Impact of Wet Etching on the Tribological Performance of 304 Stainless Steel in Hydrogen Compressor Applications - Chan-Woo Kim(김찬우); Sung-Jun Lee(이성준); Chang-Lae Kim(김창래) (Tribology and Lubricants, 2024)
Hydrogen has emerged as an eco-friendly and sustainable alternative to fossil fuels. However, the utilization of hydrogen requires high-pressure compression, storage, and transportation, which poses challenges to the durability of compressor components, particularly the diaphragm. This study aims to improve the durability of 304 stainless steel diaphragms in hydrogen compressors by optimizing their surface roughness and corrosion resistance through wet etching. The specimens were prepared by immersing 304 stainless steel in a mixture of sulfuric acid and hydrogen peroxide, followed by etching in hydrochloric acid for various durations. The surface morphology, roughness, and wettability of the etched specimens were characterized using optical microscopy, surface profilometry, and water contact angle measurements. The friction and wear characteristics were evaluated using reciprocating sliding tests. The results showed that increasing the etching time led to the development of micro/nanostructures on the surface, thereby increasing surface roughness and hydrophilicity. The friction coefficient initially decreased with increasing surface roughness owing to the reduced contact area but increased during long-term wear owing to the destruction and delamination of surface protrusions. HCl-30M exhibited the lowest average friction coefficient and a balance between the surface roughness and oxide film formation, resulting in improved wear resistance. These findings highlight the importance of controlling the surface roughness and oxide film formation through etching optimization to obtain a uniform and wear-resistant surface for the enhanced durability of 304 stainless steel diaphragms in hydrogen compressors. KCI Citation Count: 0